Global changes to the chemotherapy service during the covid-19 pandemic. (July 2021) - Chow, Man-Chie; Chambers, Pinkie; Singleton, Georgina; Patel, Jignesh; Cooper, Silvie; Mythen, Charlotte; Bautista-González, Elysse; Chisnall, Georgia; Djellouli, Nehla; Thwaites, Benjamin; Wong, Ian CK; Vindrola-Padros, Cecilia
Purpose: In response to the COVID-19 pandemic, changes to chemotherapy services were implemented as a means of managing imposed workload strains within health services and protecting patients from contracting COVID-19. Given the rapidly evolving nature of the pandemic many changes were rapidly adopted and were not substantiated by robust evidence. This study aimed to describe the changes adopted internationally to chemotherapy services, which may be used to guide future changes to treatment delivery. Methods: A survey was developed to understand the impact of COVID-19 on the delivery of systemic anti-cancer therapies (SACT). It comprised 22 questions and examined the strategies implemented during the pandemic to prioritise and protect patients receiving SACT and the participants' professional opinion of the strategies employed. The survey was available in English, Spanish and French and was distributed via professional bodies. Results: 129 responses were obtained from healthcare professionals working across 17 different countries. 45% of institutions had to implement treatment prioritisation strategies and all hospitals implemented changes in the delivery of treatment, including: reduction in treatments (69%), using less immunosuppressive agents (50%), allowing treatment breaks (14%) and switching to oral therapies (45%). Virtual clinic visits were perceived by participants as the most effective strategy to protect patients. Conclusions: The pandemic has forced chemotherapy healthcare professionals to adopt new ways of working by reducing health interactions. Many areas of research are needed following this period, including understanding patients' perceptions of risks to treatment, utilisation of oral treatments and the impact of treatment breaks on cancer outcomes.